PROGNOSTIC FACTORS TOWARD BLADDER CANCER PATIENT RECOVERY AFTER RADICAL CYSTECTOMY SURGERY - Triyaka, Rendy; Ahmad Zulfan Hendri (Indonesian Journal of Urology, 2021)
Objective: This study aimed to know independent prognostic factors to predict the recovery time of bladder cancer patients after radical cystectomy. So that it would be a consideration to determine patient feasibility before surgery and after surgery management. Material & Methods: This study was an observational analytical study with a retrospective approach to examine the relationship between pre-surgery variables of the bladder cancer patients and the duration of treatment post radical cystectomy. Results: From the results of this study, it is known that the average length of postoperative care for older patients (above 65 years) was lower when compared to patients under 65 years with averages of 17.08 and 18.03 days respectively p-value of this analysis was 0.781. Patients with low hemoglobin, albumin, and HALP scores had longer postoperative hospitalization periods but with P values of 0.384, 0.276, and 0.603, the ileal conduit has the longest hospitalization treatment period between the two other procedures, with a P-value of 0.904. It was found that the average length of postoperative care for underweight patients was 16.5 days and for patients with normal BMI was 19.59 days. The difference between these averages showed a p-value of 0.396 it is known that the average length of postoperative care for older patients (above 65 years) was lower when compared to patients under 65 years with averages of 17.08 and 18.03 days respectively. The p-value of this analysis was 0.781 it was found that patients with low hemoglobin, albumin, and HALP scores had longer postoperative treatment periods, p-value 0.384, 0.276, and 0.603. The average duration of postoperative care for patients who applied the ERAS protocol tended to be faster (15.67 days) compared to patients who did not apply the ERAS protocol (18.16 days). Nevertheless, the p-value of this difference was 0.518. Conclusion: This study concludes that there is no prognostic factor that can independently predict the duration of treatment of bladder cancer patients post-radical cystectomy. Therefore in-depth assessment of various factors is required before performing radical cystectomy to achieve the best postoperative recovery rates.